Production d'ovins et de caprins au ranch collectif d'Elangata Wuas - Peacock, C.P. (1983)
Presents a sheep and goat production study carried out in the Kajiado district of Kenya at Elangata Wuas group ranch from July 1978 to February 1981. Discusses productivity (age at first parturition, parturition interval, weight gain), mortality (preweaning death) among different age & sex groups.